Exploring the Impact of Automatic Speech Recognition on Students' Speaking Skills and Perceptions - Andi Reza Maulana; Ririn Pratiwi Suharto (Universitas Harapan Bangsa, 2024)
The speaking application developed in this research by using the technology of Automatic Speech Recognition (ASR) aims to help students practice speaking autonomously in English. The main objective is to form an interactive application named LINKS, which enhances their pronunciation, fluency, and vocabulary. The design, development, and evaluation of the application were based on survey findings from 28 participants along with principles from the ADDIE model. The findings showed that 82% of the students reported improvement in their pronunciation and speaking skills, while 96% rated the user interface and feedback system positively. The participants also found that the application gave corrective feedback and helped with self-assessment, and real-time scores presented to students which enabled them to handle mistakes much better and even boosted their confidence. Furthermore, the interactive features raised learner autonomy and engagement, demonstrating that ASR-based applications can be an effective tool for enhancing independent learning. This research, concludes that the application can be a useful tool to overcome students' problems in speaking as well may help the language learning process.